2022
DOI: 10.1186/s12645-022-00143-w
|View full text |Cite
|
Sign up to set email alerts
|

Resveratrol-loaded gold nanoparticles enhance caspase-mediated apoptosis in PANC-1 pancreatic cells via mitochondrial intrinsic apoptotic pathway

Abstract: Background Pancreatic ductal adenocarcinoma (PDAC) remains one of the most fatal malignancies. Several chemotherapies employing fluorouracil (5-FU) and gemcitabine were attempted, but the survival rate was extremely low. Resveratrol (RVT), known as a polyphenol compound and phytoalexin, was demonstrated to induce intrinsic apoptosis in cancer cells. However, its low delivery performance and efficiency at tumor sites remain an obstacle to exploit RVT as a drug. To address these problems, we bio-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 64 publications
0
7
0
Order By: Relevance
“…RSV-PVP-GNPs trigger more aggressive apoptosis via intrinsic mitochondria compared to free RSV. In preclinical trials, RSV-PVP-GNPs conjugated with AS1411 aptamer effectively suppressed tumor volume without renal toxicity [ 182 ].…”
Section: Application Of Nanoparticles To Improve the Therapeutic Pote...mentioning
confidence: 99%
“…RSV-PVP-GNPs trigger more aggressive apoptosis via intrinsic mitochondria compared to free RSV. In preclinical trials, RSV-PVP-GNPs conjugated with AS1411 aptamer effectively suppressed tumor volume without renal toxicity [ 182 ].…”
Section: Application Of Nanoparticles To Improve the Therapeutic Pote...mentioning
confidence: 99%
“…The delivery performance and anticancer efficacy of RSV were enhanced when RSV was conjugated with gold nanoparticles (Au SNPs) using polyvinylpyrrolidone as a cross-linker. Compared with free RSV, these RSV-loaded NPs reduced the proportion of necrotic cells by activating the mitochondrial intrinsic apoptotic pathway in human pancreatic cancer cells [ 195 ]. Other studies on the encapsulation of RSV in AuNPs have shown that RSV induces cell cycle arrest in MCF-7 cancer cell lines [ 196 ] and has better anti-invasive effects on human breast cancer cells than RSV alone [ 197 ].…”
Section: Rsv Modificationsmentioning
confidence: 99%
“…GNPs exhibit good stability, high thermal, optical, and electrical activity, high surface area, and multifunctionality (Amina and Guo, 2020 ), RES was biocoupled with GNPs via the cross-linking agent polyvinylpyrrolidone (RES@PVP-GNPs) to enhance the delivery performance and anti-tumor efficacy of RES (Lee et al., 2022 ). However, GNPs are usually synthesized by physical or chemical methods that may be toxic to humans.…”
Section: Nanocarriers Used For Res Deliverymentioning
confidence: 99%